Care to celebrate? - Janine Gorman (Scottish Journal of Residential Child Care, 2004)
In July 2003, the children's unit for over 12s in which I work celebrated its first birthday … Yes, celebrated! At first, however, the notion to celebrate this occasion did not sit easily with everyone.